Changes in Physical Activity Among Nursing Students Following Use of the Strava Application: A One-Group Pretest–Posttest Study - Asep Miftah; Widiawan Sukarno Ardhianto; Irfan Zakaria Permana (STIKes Budi Luhur Cimahi, 2026)
Low physical activity among nursing students is a health concern because they are expected to become future health promoters and role models for healthy behavior. Digital health promotion through fitness tracking applications may support students in monitoring and improving their physical activity. This study aimed to examine changes in nursing students' physical activity after using the Strava application as a digital health promotion medium. This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. A total of 193 nursing students completed both pretest and posttest measurements. Physical activity was measured using the Indonesian version of the International Physical Activity Questionnaire-Short Form (IPAQ-SF). Participants used the Strava application for two weeks to record and monitor their preferred physical activities. Data were analyzed using the Shapiro-Wilk normality test and the Wilcoxon signed-rank test. Before using Strava, most respondents had low physical activity, with 109 students (56.5%) in the low category, 78 students (40.4%) in the moderate category, and 6 students (3.1%) in the high category. After using Strava, the low category decreased to 70 students (36.3%), while the moderate category increased to 109 students (56.5%) and the high category increased to 14 students (7.3%). The median MET-minutes/week increased from 509.00 (IQR = 736.00; Q1-Q3 = 228.50-964.50) at pretest to 842.00 (IQR = 1139.50; Q1-Q3 = 500.50-1640.00) at posttest. The Wilcoxon signed-rank test showed a significant difference between paired pretest and posttest MET scores (Z = -8.176; p < 0.001; r = 0.59). These findings suggest that Strava may support improvements in physical activity among nursing students. However, because this study used a one-group pretest-posttest design without a control group, the findings should be interpreted as an observed association rather than definitive causal evidence.